Light and Heavy Chain Components of Gamma Globulins in Urines of Normal Persons and Patients with Agammaglobulinemia - Vaughan, John H. (1967)
A heavy chain component of γG-globulins in normal urines has the characteristics of the proteolytic digestion product, Fc-fragment. This fragment is estimated to compose up to 15% of the gamma globulins present in urines. In contrast to urinary light chains, the urinary Fc-like fragment probably represents a catabolic component in normal γG-globulin metabolism. The light chains of the urine constitute more than half the total gamma globulin present. The calculated κ/λ ratio of light chains averaged 1.9 in ten urines, but the ratio in individual urines varied widely to either side of this figure. In two adult patients with agammaglobulinemia whose sera contained less than one-hundredth the normal gamma globulin levels, the urinary Fc-like fragment was absent, whereas the light chain levels were only one-tenth the average normal level. Treatment with exogenous gamma globulins resulted in normal or near normal Fc-like fragment excretion, whereas light chain excretion was only modestly affected.